What is the Effect of Intangible Assets on Earnings of the Serbian Banking Sector? - Barjaktarović, Lidija; Stefanović, Nikola (Industrija, 2019)
Digital transformation is the permanent improvement of business processes within a bank by available digital tools and technologies in order to survive in the market. It is driven primarily by the clients’ needs, new competitors, regulations, and strategy based on the existing tradition. The aim of the paper is to determine whether there is a link between the money invested in digitalization and the achieved result of the bank through the relevant financial indicators. The results of the research show that the banking offer of alternative distribution channels’ products in the Republic of Serbia (RS) follows world trends and it can be considered developed. Furthermore, the level of investment in digitalization has a direct impact on the achieved result of the banking sector. Moreover, the banking sector generates more revenue than traditional products offered, and investments in digitalization, innovation and IT technology are inevitable if they want to survive on the market, which is, due to global trends, the need of clients and requirement of the regulator. It is certainly an imperative for all banks in RS to continue investing in education of employees and clients, improvement of business processes, and new tools in order to survive on the market and be competitive.